Peningkatan Ekonomi Ibu-Ibu PKK Desa Pesanggrahan Melalui Olahan Pisang Mentah - Desrina Yusi Irawati; Agrienta Bellanov; Ariel Julianus Pical; Ravaelino Dimas Eka Narendra ((STKIP) PGRI Tulungagung, 2023)
Pesanggrahan Village is a village in Laren District, Lamongan. The place is located on the banks of the Bengawan Solo River. Banana trees are among the flora that the locals have planted. The abundant produce of the banana garden has prompted PKK women from Pesanggrahan village to take the initiative to develop a snack product made from unripe bananas. Based on the conditions in the field, there are problems in banana chip production activities; namely, the banana slicer used is still traditional. The banana slicer is only a board with two blades that are operated manually. This condition requires a long time to complete the slicing. In addition, the slicer is not ergonomic, so it has a great chance of injuring the worker's hand. If the slicing section gets tired and lacks patience, they use a thicker slicer to finish the job quickly. A modern and ergonomic banana-slicing machine has been developed to streamline work activities and safety. The PKK in Pesanggrahan village gave the banana-slicing machine a positive review for height. It produces banana slices that are more uniformly thin and safe and cuts bananas more quickly.